Interrogatives as a pedagogical discourse strategy: Reinterpreting Propp’s narrative structure in children’s storybooks and its implications for critical literacy development - Eliya, Ixsir; Nuthihar , Rahmad; Damaianti, Vismaia S.; Seles , Susi; Aljamaliah, S. Nailul Muna; Afriani , Zelvia Liska (Universitas Ahmad Dahlan, 2026)
This study aims to reinterpret Propp’s narrative structure in children’s storybooks by positioning interrogative sentences as pedagogical discourse strategies and examining their implications for the development of children’s critical literacy. This study adopts a qualitative approach within a pedagogical discourse framework, drawing on Vladimir Propp’s model to identify narrative functions in the text. The results showed that Lomba Tebak Cepat and Bermain Teka-teki followed similar narrative patterns, repeating Propp’s functions ξ, M, and Pr eleven times. On the other hand, Buah Apa, ya? followed a different sequence—ξ – M – Pr – G – Q – N – I—with the M – Pr – G pattern appearing three times. The interrogative sentences in all three books were either total or partial and mainly informative, using the word “apa” and the Indonesian particle “-kah.” Repeating these questions helped shape new narrative patterns. Overall, Propp’s structure can be simplified as E – P – p1, p2, p3… – X – Y – R – E, showing how a mix of interrogatives and narrative functions makes these storybooks more engaging and interactive for children. The findings show that interrogative sentences function as pedagogical strategies that actively engage children in understanding the story. Through interrogative sentences, children are encouraged to think critically and use their reasoning to make sense of the text, thereby supporting their literacy development, especially in critical and reflective thinking.